Retrospective Reporting of First Employment in the Life-courses of U.S. Women - Shattuck, Rachel M. (Sociol Methodol, 2017)
We investigate the accuracy of young women’s retrospective reporting on their first substantial employment in three major, nationally-representative United States surveys, examining hypotheses that longer recall duration, employment histories with lower salience and higher complexity, and an absence of “anchoring” biographical details will adversely affect reporting accuracy. We compare retrospective reports to benchmark panel survey estimates for the same cohorts. We find that sociodemographic groups—notably non-Hispanic White women and women with college-educated mothers—whose early employment histories at these ages are in aggregate more complex (multiple jobs) and lower in salience (more part-time jobs), are more likely to omit the occurrence of their first substantial job or employment, and to misreport their first job or employment as occurring at an older age. We also find that retrospective reports are skewed towards overreporting longer, therefore more salient, later jobs over shorter, earlier jobs. The relatively small magnitudes of differences, however, indicate that the retrospective questions nevertheless capture these summary indicators of first substantial employment reasonably accurately. Moreover, these differences are especially small for groups of women who are more likely to experience labor-market disadvantage, and for women with early births.